2012
DOI: 10.1128/aem.01594-12
|View full text |Cite
|
Sign up to set email alerts
|

Predatory Bacteria as Natural Modulators of Vibrio parahaemolyticus and Vibrio vulnificus in Seawater and Oysters

Abstract: dThis study shows that naturally occurring Vibrio predatory bacteria (VPB) exert a major role in controlling pathogenic vibrios in seawater and shellfish. The growth and persistence of Vibrio parahaemolyticus and Vibrio vulnificus were assessed in natural seawater and in the Eastern oyster, Crassostrea virginica. The pathogens examined were V. vulnificus strain VV1003, V. parahaemolyticus O1:KUT (KUT stands for K untypeable), and V. parahaemolyticus O3:K6 and corresponding O3:K6 mutants deficient in the toxRS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
89
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 45 publications
(45 reference statements)
4
89
1
Order By: Relevance
“…The fact that the experimental results concerned native predators in NWs adds relevance to the findings. Other investigators using different experimental models have also reported a reduction of prey bacteria by Halobacteriovorax and the potential of the predators to affect the mortality of susceptible bacterial populations in aquatic systems (Richards et al, 2012;Li et al, 2014;Wen et al, 2014). Richards et al (2012) used several strains of V. parahaemolyticus and a strain of V. vulnificus as amendments to a natural seawater sample and observed a decline in their numbers along with an increase in Halobacteriovorax as we observed in the experiments described in this report.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The fact that the experimental results concerned native predators in NWs adds relevance to the findings. Other investigators using different experimental models have also reported a reduction of prey bacteria by Halobacteriovorax and the potential of the predators to affect the mortality of susceptible bacterial populations in aquatic systems (Richards et al, 2012;Li et al, 2014;Wen et al, 2014). Richards et al (2012) used several strains of V. parahaemolyticus and a strain of V. vulnificus as amendments to a natural seawater sample and observed a decline in their numbers along with an increase in Halobacteriovorax as we observed in the experiments described in this report.…”
Section: Discussionsupporting
confidence: 77%
“…The findings of this and other studies demonstrating the impact of BALO predation in aquatic systems (Li et al, 2011;Richards et al, 2012;Wen et al, 2014) argues for recognition of their potential role as biological agents of bacterial mortality along with viruses and protists. Johnke et al (2014) have made a strong case for assessing the potential of multiple micro-predators rather than focusing on a single predator, as many previous studies have done.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Predation by BALOs also releases nutrients (Martínez et al, 2013), affecting biogeochemical cycling and production in nutrient-limited environments, similar to the effects of phage (Fuhrman, 1999;Brussaard et al, 2008). In contrast to viruses, which are the most abundant biological entity in the marine environment and maintain abundances approximately in an order of magnitude greater than their hosts, BALOs do not need to be in high initial concentrations in the environment to drive significant bacterial mortality of their prey (Richards et al, 2012;Williams et al, 2016). One group of Bdellovibrionales, the marine Halobacteriovorax, are broadly distributed in marine waters across temperature, salinity and pH gradients (Pineiro et al, 2007).…”
Section: Introductionmentioning
confidence: 99%